Uji stabilitas fisik formulasi sediaan sirup infusa daun seledri (Apium graveolens L.) dengan larutan pemanis daun stevia (Stevia rebaudiana) - Dewi, Indri Kusuma; Alif, Salsa Billa Nur; Ridlo, Achmad (Universitas Muhammadiyah Magelang, 2024)
One of the cardiovascular diseases is commonly known as hypertension, which is high blood pressure. It is recognized as a cause of death and is often referred to as the